Dataset: Introducing a practice perspective on monitoring for adaptive management - West, Simon; Beilin, Ruth; Wagenaar, Hendrik (Stockholm University, 2019)
This research project explored the science and practice of ecological monitoring for adaptive management. We conducted a qualitative case study of a project intended to develop an adaptive management approach to vegetation restoration in the ‘Wildlands National Park,’ Australia (hereafter referred to as 'the Wildlands AM project').

‘Wildlands’ is a pseudonym – all place and personal names associated with the AM project have been changed to protect the participants’ anonymity.

Our qualitative case study of the Wildlands AM project adopted a theoretical perspective rooted in practice theory (Cook, S.D.M. and Wagenaar, H. 2012. 'Navigating the Eternally Unfolding Present: Towards an Epistemology of Practice. The American Review of Public Administration 42(1): 31-38).

Data collection methods consisted of one observation event and open-ended qualitative interviews.

The observation event consisted of observing a three-day scientific field trip to the Wildlands National Park undertaken by scientists in the Wildlands AM project. The field trip was a pilot study that was intended to contribute information to a broader process of developing an adaptive management approach to vegetation restoration at Wildlands.

Follow-up, open-ended qualitative interviews were conducted with most Wildlands AM project participants, including scientists on the field trip and representatives of the Wildlands management authority. These interviews tool place over a period of six months following the field trip as the scientists were writing up a final report to the management authority.

The data corpus was analyzed using deductive thematic analysis, where a coding scheme was devised from pre-existing theoretical constructs (Cook and Wagenaar 2012) and applied to the written interview transcripts and field notes using Nvivo for Mac qualitative data analysis software.

The fully anonymised dataset stored here contains the written field notes taken during the observation event; the written transcripts of the qualitative interviews; a summary description of the characters that appear in the data corpus and their roles in relation to the adaptive management project; the qualitative coding scheme used to analyse the data; and the participant information sheet and participant consent form provided to participants prior to each interview.

Further contextual, methodological and conceptual details that may help with the interpretation of this dataset are available in the associated scientific paper: West, S., Beilin, R. & Wagenaar, H. 2019. Introducing a practice perspective on adaptive management. People and Nature, https://doi.org/10.1002/pan3.10033.
Keywords: Earth and Environmental Sciences; Social Sciences; adaptive management; environmental monitoring; evidence-based conservation; structured decision-making; practice theory; pragmatist philosophy; relational thinking; science-policy interface; applied ecology; Transcribed qualitative interview data;Field notes;Qualitative coding frame;Study information sheet;Study consent form; Social Sciences; Samhällsvetenskap; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap